Neuroserpin: a selective inhibitor of tissue-type plasminogen activator in the central nervous system - Yepes, Manuel; Lawrence, Daniel A. (Thrombosis and Haemostasis, 2004)
Neuroserpin is a member of the serine proteinase inhibitor (serpin) gene family that reacts preferentially with tissue-type plasminogen activator (tPA) and is primarily localized to neurons in regions of the brain where tPA is also found. Outside of the central nervous system (CNS) tPA is predominantly found in the blood where its primary function is as a thrombolytic enzyme. However, tPA is also expressed within the CNS where it has a very different function, promoting events associated not only with synaptic plasticity but also with cell death in a number of settings, such as cerebral ischemia and seizures. Neuroserpin is released from neurons in response to neuronal depolarization and plays an important role in the development of synaptic plasticity. Following the onset of cerebral ischemia there is an increase in both tPA activity and neuroserpin expression in the area surrounding the necrotic core (ischemic penumbra), and treatment with neuroserpin following ischemic stroke or overexpression of the neuroserpin gene results in a significant decrease in the volume of the ischemic area as well as in the number of apoptotic cells. TPA activity and neuroserpin expression are also increased in specific areas of the brain by seizures, and treatment with neuroserpin slows the progression of seizure activity throughout the CNS and results in significant neuronal survival in the hippocampus. Mutations in human neuroserpin result in a form of autosomal dominant inherited dementia which is characterized by the presence of intraneuronal inclusion bodies and is known as Familial Encephalopathy with Neuroserpin Inclusion Bodies.
Keywords: Neuroserpin; tissue-type plasminogen activator; cerebral ischemia; seizures; dementia